Integrated Marketing Communication Effectiveness Valuation Tools: A Thirty-Year Bibliometric Analysis - A. Zh. Orazayev; V. Garkavenko (Экономика: стратегия и практика)
In the context of digital transformation and media polarization, companies are increasingly resorting to integrated marketing communications (hereinafter – IMC) in order to ensure brand consistency and improve the effectiveness of communication strategies. This scientific study aims to conduct a bibliometric analysis of scientific literature on evaluating the effectiveness of IMC, in order to identify key theoretical and methodological approaches, dominant thematic areas, and the evolution of metrics from 1991 to 2021. The study utilizes bibliometric analysis with the Bibliometrix tool in the R environment and a sample of 320 publications from the Scopus database as its source base. The empirical basis for this research is an array of 30 peer-reviewed articles on BMI assessment and measurement selected from the same database, covering a period from 1. The research includes an analysis of the ratios of keywords, co-citation mapping and analysis of publication dynamics in order to identify thematic clusters, leading researchers and the intellectual structure of scientific fields. The results allowed us to identify five main research areas: (1) conceptual foundations of BMI; (2) brand capital and consumer behaviour; (3) valuation models and ROI indicators; (4) integration of digital media; and (5) BMI in the global and emerging market. It was found that over the last three decades there has been a shift from theoretical discussion to applied research, with particular focus on digital transformation. Future research should focus on developing an efficiency index, examining the long-term effects of integrated communication and its adaptation to digital and crosscultural environments.